2022
DOI: 10.1029/2021gl097227
|View full text |Cite
|
Sign up to set email alerts
|

Successive Dipolarization Fronts With a Stepwise Electron Acceleration During a Substorm in Saturn's Magnetotail

Abstract: Studies on substorms originated from the discovery of consistent patterns of auroral activity in Earth's ionosphere (Akasofu, 1964). After decades of intense studies, several features of Earth's substorms have become well known (e.g., Haerendel, 2015). At the beginning of a substorm, dayside magnetopause reconnection occurs, and the corresponding magnetic flux is transported to the lobes and loaded into the magnetotail (Dungey, 1961). Then, the increased magnetic pressure within the lobes thins the central cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…RFs play an important role in magnetotail dynamics (e.g., Angelopoulos et al, 2013;Artemyev et al, 2020;Huang et al, 2015a;Jackman et al, 2014;Sundberg et al, 2012). Ion acceleration (e.g., Li et al, 2014;Zhou et al, 2015) as well as electron acceleration (Xu et al, 2020) associated with TRFs have also been investigated. As for our case, the electrons within the 251-905 eV energy range gathered around 90° behind the TRF and the FPR is a growing type, which probably results from betatron acceleration (Fu et al, 2011(Fu et al, , 2012b.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…RFs play an important role in magnetotail dynamics (e.g., Angelopoulos et al, 2013;Artemyev et al, 2020;Huang et al, 2015a;Jackman et al, 2014;Sundberg et al, 2012). Ion acceleration (e.g., Li et al, 2014;Zhou et al, 2015) as well as electron acceleration (Xu et al, 2020) associated with TRFs have also been investigated. As for our case, the electrons within the 251-905 eV energy range gathered around 90° behind the TRF and the FPR is a growing type, which probably results from betatron acceleration (Fu et al, 2011(Fu et al, , 2012b.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…One possible mechanism to form TRFs is the magnetic reconnection between the crustal field and the draped field in the magnetotail. Using the method suggested by Xu et al (2017), the magnetic field topology is identified as shown in Figure S3 of Supporting Information S1. It seems that there are mostly draped fields around the current sheet in our event.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…DFs are believed to efficiently lead to particle heating and acceleration (Fu et al 2011;Liu et al 2017;Zhong et al 2019a;Ma et al 2020). In Saturnʼs magnetotail, Xu et al (2022) demonstrated that electrons are stepwise accelerated by successive DFs during substorms. The DF has also been suggested to be associated with electron and ion heating in the Jovian magnetotail (Kasahara et al 2011).…”
Section: Introductionmentioning
confidence: 99%